Proses Pelaksanaan Penilaian Hasil Pembelajaran Pendidikan Jasmani Anak Tuna Rungu di SMALB Negeri Pembina Pekanbaru - Sari, Merlina (Journal Sport Area, 2018)
Physical education for children with hearing impairment should be implemented by applying appropriate adaptive learning strategies to support the achievement of expected goals, because children with hearing or hearing impairment can not process information as normal children. Thus, in the implementation of learning teachers should be able to build good communication Based on the results of observations that the authors do to students with hearing impaired Private Junior High School (SMPLB) as a city Pekanbaru. Some problems are found, namely the lack of knowledge of students in the field of physical education because when the students' learning tends to be pensive and not pay attention to the teacher, when the assessment begins students can not perform the movement that is taught by the teacher because in the learning process students tend not to notice, and the student body tends to stiff when practicing movements that teachers teach. From the results of data collected and analyzed, although there are teachers who have not conducted a good assessment but the final end of the sample collected is the implementation of assessment in the physical education field of the private junior high school deaf students (SMPLB) in Pekanbaru city well done